2010
DOI: 10.1007/s11739-010-0483-5
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and neurohumoral profile in patients with different types of hypertension in pregnancy

Abstract: Hypertension in pregnancy is a frequent disorder that includes a spectrum of conditions. We aimed at comparatively evaluating the hemodynamic, echocardiographic and biohumoral profile of a sample of pregnant Caucasian women with different form of pregnancy-related hypertension. We enrolled 39 non-hypertensive pregnant women (NP), 26 with Chronic HBP in pregnancy (CH), 24 with gestational hypertension (G-PIH), and 33 with pre-eclampsia. We recorded and compared blood pressure (BP), echocardiographic parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In nondiabetic women, increased levels of ANP and brain natriuretic peptide are seen in late pregnancy when the diagnosis of pre-eclampsia has been established (39,40). In a small, prospective series of women with type 1 diabetes followed throughout pregnancy at our center, pre-eclampsia developed in six women (7%) with significantly higher ANP levels at 9 gestational weeks compared with women not developing pre-eclampsia.…”
Section: Pre-eclampsia and Vasoactive Markersmentioning
confidence: 94%
“…In nondiabetic women, increased levels of ANP and brain natriuretic peptide are seen in late pregnancy when the diagnosis of pre-eclampsia has been established (39,40). In a small, prospective series of women with type 1 diabetes followed throughout pregnancy at our center, pre-eclampsia developed in six women (7%) with significantly higher ANP levels at 9 gestational weeks compared with women not developing pre-eclampsia.…”
Section: Pre-eclampsia and Vasoactive Markersmentioning
confidence: 94%
“…This is consistent with remodeling patterns seen in early hypertension without evidence of age or ethnic specificity in the women evaluated so far. 30 Although several other studies have also demonstrated LV dysfunction, [41][42][43][44][45][46][47][48] increased aortic stiffness, [49][50][51] and reduced venous capacity in preeclampsia, 52 it remains difficult to truly understand by noninvasive methods whether decreased LV performance with preeclampsia affected myocardial contractility. Indeed, each echocardiographic index is only a surrogate of the true myocardial state, and it is invariably affected by loading conditions, heart rate, and cardiac geometry in a lesser or greater extent.…”
Section: The Cardiovascular Changes At Presentation With Preeclampsiamentioning
confidence: 99%
“…It has been shown that hemodynamic profile differs with the type of hypertension in pregnancy. 33 Hemodynamic assessment will need to be included in further studies with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%